Comparison of student achievement between digital classes and regular classes in social studies subjects - Salsabiil*, Salsabiil; Zakaria, Zakaria; Sakdiyah, Sakdiyah (Universitas Syiah Kuala, 2024)
The learning process in the 21st century has urged educators to be more creative and innovative regarding learning models, methods, and media. One of the approaches to enhance learning effectiveness is the integration of digital technology into the learning process, realized through digital class programs. The objective of this study was to assess student learning achievements in digital classes compared to regular classes and determine any differences in student performance between the two settings. This study employed a quantitative approach with a comparative research design. The population consisted of 190 students, and a purposive sampling technique was applied, considering the equivalence of abilities among regular class students. The sample comprised 31 digital class students and 34 regular class students at State Islamic Junior High School (MTsN) 4 of Banda Aceh City in 2023. The process of data collection involved interviews, observation, and documentation. The analysis included normality and homogeneity tests as prerequisites, as well as an independent sample t-test for hypothesis testing. The overall average score for digital class students was 71.17, while regular class students scored an average of 73.16. The difference in average scores between digital and regular classes was 1.99. In the t-test, the calculated t-value was -0.904, with a critical t-value of 1.998 at a significance level of 0.05 and df=63. As the calculated t-value (-0.904) was less than the critical t-value (1.998), the hypothesis in this study was rejected. The findings from the average scores and t-test value indicated that there was no significant difference in student learning achievement between digital and regular classes in Social Science Subject at State Islamic Junior High School (MTsN) 4 of Banda Aceh. This can happen due to several factors such as students ability to use digital devices is still limite, so they do not fully understand the subject matter and internet facilities is often difficult to access.